Single-cell atlas of the tumor immune microenvironment across syngeneic murine models - Wang, Jia; Jiang, Bin; Deng, Minjuan; Yan, Han; Zhang, Pei; Jin, Wei; Shen, Zhirong (Frontiers in Immunology, 2025)
The tumor immune microenvironment plays a critical role in tumor progression and responses to immunotherapy. Nevertheless, its cellular complexity and heterogeneity remain incompletely understood. In this study, we employed high-resolution single-cell RNA sequencing on CD45+ immune cells isolated from ten syngeneic murine tumor models, representing seven distinct cancer types under treatment-naïve conditions, thereby enabling a comprehensive profiling of tumor-infiltrating immune cells. We identified seven principal immune cell populations and provided an in-depth characterization of T cells, NK/innate lymphoid cells, dendritic cells, monocytes/macrophages, and neutrophils. Cross-species analyses further delineated conserved immune cell states and transcriptomic features within the T cell and monocyte/macrophage compartments that are shared across syngeneic models and human tumors. To investigate the functional relevance of the predominant monocyte/macrophage compartment and the notable presence of neutrophils in syngeneic tumors, we evaluated responses to anti-PD-1 therapy across various models and analyzed the enrichment of monocyte/macrophage subsets in tumors that responded to treatment. Furthermore, we conducted neutrophil depletion experiments using anti-Ly6G antibodies, administered both as monotherapy and in combination with PD-1 blockade. Remarkably, an interferon-stimulated gene-high (ISGhigh) monocyte subset was significantly enriched in models responsive to anti-PD-1 therapy. Neutrophil depletion resulted in variable antitumor effects across models but failed to enhance the efficacy of PD-1 blockade. In summary, our single-cell profiling offered a detailed atlas of the immune microenvironment across multiple syngeneic mouse tumor models, thereby enabling rational model selection for immuno-oncology studies. We uncovered an ISGhigh monocyte subset enriched in anti-PD-1 responsive models, and showed the context-dependent effects of neutrophil depletion on tumor immunity and immunotherapy, underscoring the heterogeneity and functional divergence of immune cell sublineages.